Why the Bible began an alternative history of scripture and its origins - Wright, Jacob L. 1973- (Cambridge, United Kingdom New York, NY, USA Cambridge University Press, 2023)
Why did no other ancient society produce a text remotely like the Bible? That a tiny, out of the way community, could have produced a text so determinative for peoples across the globe seems improbable.For Jacob Wright, the Bible is not only a testimony of survival, but also an unparalleled achievement in human history. Forged during Babylonian exile after the shattering destruction of Jerusalem, it makes not victory but total humiliation the foundation of a new idea of belonging. Lamenting the destruction of their homeland, scribes who composed the Bible turned to the golden ages of the past, reflecting deeply on abject failure. More than just religious scripture, the Bible is a resonant blueprint for the inspiring creation of a nation. As a response to catastrophe, it offers a powerful, message of hope and restoration that is unique in the Ancient Near Eastern and Greco-Roman worlds. Wright's Bible is thus a social, political, and even economic roadmap - one that enabled a small and obscure community located on the periphery of leading civilizations and empires, not just to come back from the brink, but ultimately to shape the world's destiny. The Bible speaks ultimately of being
Title from publisher's bibliographic system (viewed on 13 Jul 2023)
Keywords: Bible -- History; Jews -- History -- To 70 A.D